Drug–Phospholipid Co-Amorphous Formulations: The Role of Preparation Methods and Phospholipid Selection - Keyoomars Khorami; Sam Darestani Farahani; Anette Müllertz; Thomas Rades (Pharmaceutics)
Background/Objectives: This study aims to broaden the knowledge on co-amorphous phospholipid systems (CAPSs) by exploring the formation of CAPSs with a broader range of poorly water-soluble drugs, celecoxib (CCX), furosemide (FUR), nilotinib (NIL), and ritonavir (RIT), combined with amphiphilic phospholipids (PLs), including soybean phosphatidylcholine (SPC), hydrogenated phosphatidylcholine (HPC), and mono-acyl phosphatidylcholine (MAPC). Methods: The CAPSs were initially prepared at equimolar drug-to-phospholipid (PL) ratios by mechano-chemical activation-based, melt-based, and solvent-based preparation methods, i.e., ball milling (BM), quench cooling (QC), and solvent evaporation (SE), respectively. The solid state of the product was characterized by X-ray powder diffraction (XRPD), polarized light microscopy (PLM), and differential scanning calorimetry (DSC). The long-term physical stability of the CAPSs was investigated at room temperature under dry conditions (0% RH) and at 75% RH. The dissolution behavior of the CCX CAPS and RIT CAPS was studied. Results: Our findings indicate that SE consistently prepared CAPSs for CCX-PLs, FUR-PLs, and RIT-PLs, whereas the QC method could only form CAPSs for RIT-PLs, CCX-SPC, and CCX-MAPC. In contrast, the BM method failed to produce CAPSs, but all drugs alone could be fully amorphized. While the stability of each drug varied depending on the PLs used, the SE CAPS consistently demonstrated the highest stability by a significant margin. Initially, a 1:1 molar ratio was used for screening all systems, though the optimal molar ratio for drug stability remained uncertain. To address this, various molar ratios were investigated to determine the ratio yielding the highest amorphous drug stability. Our results indicate that all systems remained physically stable at a 1.5:1 ratio and with excess of PL. Furthermore, the CAPS formed by the SE significantly improves the dissolution behavior of CCX and RIT, whereas the PLs provide a slight precipitation inhibition for supersaturated CCX and RIT. Conclusions: These findings support the use of a 1:1 molar ratio in screening processes and suggest that CAPSs can be effectively prepared with relatively high drug loads compared to traditional drug–polymer systems. Furthermore, the study highlights the critical role of drug selection, the preparation method, and the PL type in developing stable and effective CAPSs.